Perlindungan Hukum bagi Pihak Ketiga atas Sertifikat Hak Milik Tanah yang Dijadikan Jaminan Kredit - Musyarif, Muhammad Abdul Hakim Aliy Ainun; Lyanthi, Merline Eva (CV. Era Digital Nusantara, 2025)
This writing journal aims to study and find out the legal protection obtained by third parties as owners of land ownership certificates as replacement collateral for debtors at the bank. The problem taken in this journal is: How is Legal Protection for Mortgage Owners as Replacement Collateral by Debtors in Banks. This journal research uses a normative juridical approach method with the writing reference being positive legal rules in Indonesia. After that, carry out a normative analysis and use legal materials such as the 1945 Constitution, the Civil Code, statutory regulations, mortgage rights, legal expert opinions, and related concepts. This research is expected to focus on legal protection for third parties as owners of collateral/replacement collateral guaranteed by debtors, as positive legal provisions and debtor settlements harm third parties as owners of replacement objects. So it can be concluded in this paper that there are no provisions that prohibit other parties or third parties (other than creditors and debtors) from pledging their objects, but the owner of the collateral object is prone to being harmed. If another party as the owner of the collateral object feels that their rights have been violated, they will receive legal protection, both criminal and civil, and can be pursued through litigation or non-litigation.